Blood pressure and the contractility of a human leg muscle. (4th October 2013) - Luu, Billy L.; Fitzpatrick, Richard C.
Key points: At identical activation, muscle force production in a small, non‐postural hand muscle that normally operates near heart level is sensitive to physiological changes in perfusion pressure. Here we investigate how perfusion pressure affects muscle contractility in a large leg muscle that is subject to high hydrostatic pressures in its normal role. We show that this large postural muscle and the small hand muscle have similar perfusion–contractility relationships, and that changes in local perfusion and systemic blood pressure produce proportionately the same effects on muscle contractility. The rapid and reversible modulation of contractility by perfusion pressure may be explained by interstitial [K + ] that depends on the balance between energy‐dependent processes in the myocyte and passive vascular removal. These results help explain how blood pressure is controlled through the pressor response during exercise and how muscle force production and fatigue varies in different postures. Abstract These studies investigate the relationships between perfusion pressure, force output and pressor responses for the contracting human tibialis anterior muscle. Eight healthy adults were studied. Changing the height of tibialis anterior relative to the heart was used to control local perfusion pressure. Electrically stimulated tetanic force output was highly sensitive to physiological variations in perfusion pressure showing a proportionate change in force output of 6.5% per 10 mmHg. This perfusion‐dependent change in contractility begins within seconds and is reversible with a 53 s time constant, demonstrating a steady‐state equilibrium between contractility and perfusion pressure. These stimulated contractions did not produce significant cardiovascular responses, indicating that the muscle pressor response does not play a major role in cardiovascular regulation at these workloads. Voluntary contractions at forces that would require constant motor drive if perfusion pressure had remained constant generated a central pressor response when perfusion pressure was lowered. This is consistent with a larger cortical drive being required to compensate for the lost contractility with lower perfusion pressure. The relationship between contractility and perfusion for this large postural muscle was not different from that of a small hand muscle (adductor pollicis) and it responded similarly to passive peripheral and active central changes in arterial pressure, but extended over a wider operating range of pressures. If we consider that, in a goal‐oriented motor task, muscle contractility determines central motor output and the central pressor response, these results indicate that muscle would fatigue twice as fast without a pressor response. From its extent, timing and reversibility we propose a testable hypothesis that this change in contractility arises through contraction‐ and perfusion‐dependent changes in interstitial K + concentration.